2023
DOI: 10.1200/op.22.00386
|View full text |Cite
|
Sign up to set email alerts
|

A Learning Health System Approach to Cancer Survivorship Care Among LGBTQ+ Communities

Abstract: PURPOSE: Lesbian, gay, bisexual, transgender, and queer (LGBTQ+) individuals who receive primary care services at community health centers are often referred to external specialty care centers after cancer diagnosis, upon which primary care services are disrupted and may be discontinued because of gaps in communication between primary and oncologic care providers. This qualitative study evaluated barriers and facilitators to effective care coordination for LGBTQ+ patients with cancer and the utility of a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…21 Maintaining clear roles and responsibilities becomes more complex in MTSs, and many things can fall in the cracks between teams, even among the main and satellite locations of the same system. 20 Therefore, mechanisms such as the 4R Oncology models (Dunne, Liu) 22,23 prove beneficial.…”
Section: What Competencies Are Required?mentioning
confidence: 99%
“…21 Maintaining clear roles and responsibilities becomes more complex in MTSs, and many things can fall in the cracks between teams, even among the main and satellite locations of the same system. 20 Therefore, mechanisms such as the 4R Oncology models (Dunne, Liu) 22,23 prove beneficial.…”
Section: What Competencies Are Required?mentioning
confidence: 99%
“…Despite numerous calls for a more patient-centered cancer care delivery system, technologies to care delivery remain primarily in the hands of clinicians, with few meaningful patient contributions. More inclusive models of health care teams rightly include patients and families from diverse backgrounds (eg, Medicaid/Medicare and LGBTQ1 communities) [6][7][8] When considering implementation, clinicians have reported adverse experiences as practices introduce new technology. In a multisite study, clinicians reported suboptimal technology training that technology is additive-as opposed to substitutive-to workloads and that team members adopt technology unevenly, which collectively result in unreliable system processes and outcomes.…”
mentioning
confidence: 99%
“…Despite numerous calls for a more patient-centered cancer care delivery system, technologies to care delivery remain primarily in the hands of clinicians, with few meaningful patient contributions. More inclusive models of health care teams rightly include patients and families from diverse backgrounds (eg, Medicaid/Medicare and LGBTQ+ communities) 6-8 as active and essential members of the cancer care team. Currently, patient and caregiver technology use to navigate care remains largely transactional.…”
mentioning
confidence: 99%